M+20-2m=9m-6

Simple and best practice solution for M+20-2m=9m-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for M+20-2m=9m-6 equation:


Simplifying
M + 20 + -2m = 9m + -6

Reorder the terms:
20 + M + -2m = 9m + -6

Reorder the terms:
20 + M + -2m = -6 + 9m

Solving
20 + M + -2m = -6 + 9m

Solving for variable 'M'.

Move all terms containing M to the left, all other terms to the right.

Add '-20' to each side of the equation.
20 + M + -20 + -2m = -6 + -20 + 9m

Reorder the terms:
20 + -20 + M + -2m = -6 + -20 + 9m

Combine like terms: 20 + -20 = 0
0 + M + -2m = -6 + -20 + 9m
M + -2m = -6 + -20 + 9m

Combine like terms: -6 + -20 = -26
M + -2m = -26 + 9m

Add '2m' to each side of the equation.
M + -2m + 2m = -26 + 9m + 2m

Combine like terms: -2m + 2m = 0
M + 0 = -26 + 9m + 2m
M = -26 + 9m + 2m

Combine like terms: 9m + 2m = 11m
M = -26 + 11m

Simplifying
M = -26 + 11m

See similar equations:

| -9x+22+7x+11=1 | | -8(8x-1)+2(-9+2x)+x= | | 8a+3a+8=9a-2a-16 | | 25/2 | | -3m-6=5m-3 | | x/100=45/360 | | (3x+10)+(2x)=180 | | 20+4=7+4((-6)+5) | | Log(x^2-1/x)^3 | | (3x)+7=13 | | -6a+3a-13=0 | | 6c+20=4c | | 8z(6y+10z)+80z=0 | | 4x-12-6x+21=-1 | | 2(x-16)=x+5+11 | | 4m-6=3m+11 | | 2x+4y=1104 | | x+2.9=11.6 | | 7x+5y-2y= | | bhg=2x-30whatisx | | f(x)=x^2+10x-16 | | 5(x+7)=3x+47 | | bhg=2x-30 | | 3x+3z=6+8y | | 4x-3=7+3x | | 3cot(x)=1 | | 4x+3=-5+20 | | 64-s= | | -150x+3271567812785361985=5 | | 3/4x-1/4=3/4 | | 7x+4=x-4 | | 5.25m=-73.5 |

Equations solver categories